Obsessive-Compulsive Symptoms in Schizophrenia - De Haan, Lieuwe; Schirmbeck, Frederike; Zink, Mathias (Springer International Publishing : Imprint: Springer, 2015)
This book summarizes scientific advances in our understanding of the interrelationship between obsessive-compulsive symptoms (OCS) and schizophrenia and reflects on the implications for future research directions. In addition, guidelines are provided on practical assessment, diagnosis, and treatment interventions, covering both pharmacotherapy and psychotherapy. Full account is taken of the fact that the variable clinical presentation regarding time of onset and course of OCS in patients with schizophrenia strongly suggests the need for a perspective that recognizes heterogeneous subgroups and diverse neurobiological explanations. Research-based multidimensional conceptual frameworks are accordingly provided relating to the co-occurrence of the disorders, incorporating recent epidemiological, neurocognitive, neurogenetic, and pharmacodynamic findings. Obsessive-Compulsive Symptoms in Schizophrenia has been written by an international team of experts who offer insights gained through their extensive experience. It will be an invaluable guide to this frequent and clinically important comorbidity and will be particularly useful for mental health practitioners.